Sequencing Multiple Cotton Genomes Reveals Complex Structures and Lays Foundation for Breeding - Pan, Yuxin; Meng, Fanbo; Wang, Xiyin (Frontiers in Plant Science, 2020)
Cotton is a major fiber plant, which provides raw materials for clothing, protecting humans from the harsh environment of cold or hot weathers, enriching the culture and custom of human societies. Due to its importance, the diploid and tetraploid genomes of different cotton plants have been repeatedly sequenced to obtain their complete and fine genome sequences. These valuable genome data sets revealed the evolutionary past of the cotton plants, which were recursively affected by polyploidization, with a decaploidization contributing to the formation of the genus Gossypium, and a neo-tetraploidization contributing to the formation of nowadays widely cultivated cotton plants. Post-polyploidization genome instability resulted in numerous structural changes of the genomes, such as gene loss, DNA inversion and translocation, illegitimate recombination, and accumulation of repetitive sequences, and functional innovation accompanied by elevated evolutionary rates of genes. Many these changes have been asymmetric between subgnomes of the tetraploid cottons, rendering their divergent profiles of biological regulation and function. The availability of whole-genome sequences has now paved the way to identify and clone functional genes, e.g., those relating to fiber development, and to enhance breeding efforts to cultivate cottons to produce high-yield and high-quality fibers, and to resist environmental and biological stress.